Immigration policy : a tricky business. - MUNOZ, Cecilia (1993)
Identifies three major tasks faced by the Clinton Aministration : it must come up with guidelines for a generous refugee and asylum policy; it must confront the failed employer-sanctions policy and the massive employment discrimination that is its chief by-product; and it must devise a system for allocating visas which promotes family reunification and protects domestic labour interests within the United States.